Pengaruh Transparansi dan Literasi Zakat terhadap Pengumpulan Dana Zakat di Indonesia - Ahmad Fatoni (FEB Universitas Sultan Ageng Tirtayasa, 2022)
This study aims to examine the effect of zakat transparency and literacy on zakat fund collection in Indonesia. This research is a quantitative research using time series data. Through purposive sampling method, a sample of 29 provinces in Indonesia was taken. The type of data used is secondary data, namely data in 2020. The results show that the transparency index of zakat management organizations has a positive and significant influence on the collection of zakat funds. However, the zakat literacy index has no effect on the collection of zakat funds in Indonesia.